Erbium‐Ion‐Doped Tellurite Glass Fibers and Waveguides—Devices and Future Prospective: Part II. (6th May 2013) - Irannejad, Mehrdad; Fernandez, Toney; Joshi, Purushottam; Zhao, Zhanxiang; Lousteau, Joris; Richards, Billy; Jose, Gin; Jha, Animesh
Abstract : Following on from Part I of this review article that focuses on the suitability of Er 3+ ‐doped tellurium oxide glass for optical amplification in fiber, this Part II article describes how the fiber gain data were then employed to engineer amplification in waveguides, which can be integrated with semiconductor pump sources. The gain characteristics and bandwidth of a phosphate modified tellurite waveguide formed on a GaAs substrate are discussed. The limiting structural compatibility of Er 3+ ‐doped tellurite glass with polydimethylsiloxane polymer for active–passive integration is overcome by adopting a nanoscale super‐lattice approach for waveguide engineering.